Dielectric behavior of PVDF/POMA blends that have a low doped POMA content - Gregorio, R.; Malmonge, L. F.; Ferreira, GFL; dos Santos, W. N.; Mattoso, LHC (Wiley-Blackwell, 2003)
The real (epsilon') and imaginary (epsilon) components of the complex permittivity of blends of PVDF [poly(vinylidene fluoride)] with POMA [poly(o-methoxyaniline)] doped with toluenosulfonic acid (TSA) containing 1, 2.5, and 5 wt % POMA-TSA were determined in the frequency interval between 10(2) and 3 X 10(6) Hz and in the temperature range from -120 up to 120degreesC. It was observed that the values of epsilon' and epsilon had a greater increase with the POMA-TSA content and with a temperature in the region of frequencies below 10 kHz. This effect decreased with frequency and it was attributed to interfacial polarization. This polarization was caused by the blend heterogeneity, formed by conductive POMA-TSA agglomerates dispersed in an insulating matrix of PVDF. The equation of Maxwell-Garnett, modified by Cohen, was used to evaluate the permittivity and conductivity behavior of POMA-TSA in the blends. A strong decrease was observed in POMA-TSA conductivity in the blend, which was bigger the lower the POMA-TSA content in the blend. This decrease could have been caused either by the POMA dedoping during the blend preparation process or by its dispersion into the insulating matrix. (C) 2002 Wiley Periodicals, Inc.
Keywords: PVDF; conducting polymer; polyaniline; blend; permittivity; interfacial polarization